Modeling of transcatheter aortic valve replacement: Patient specific vs general approaches based on finite element analysis; Computers in Biology and Medicine; Vol. 69 - Ovcharenko E. A.; Klyshnikov K. U.; Yuzhalin A. E.; Savrasov G. V.; Kokov A. N.; Batranin A. V. Andrey Viktorovich; Ganyukov V. I.; Kudryatseva Yu. A. (2016, 2016)
Title screen